Cyclic Nucleotide Phosphodiesterase Activity in Barley Seeds - Vandepeute, Jozef (1973)
Barley seeds (Hordeum vulgare L. cv. Himalaya) contain an enzymatic activity which catalyzes the hydrolysis of adenosine cyclic 3′: 5′-monophosphate and adenosine cyclic 2′: 3′-monophosphate. A large portion of the enzymatic activity is present in the dry seed, existing in both soluble and particulate form. Secretion of the soluble phosphodiesterase from embryoless seeds is enhanced by gibberellic acid and inhibited by abscisic acid, dinitrophenol, and cycloheximide. Attempts to isolate or detect a phosphodiesterase which specifically hydrolyzes adenosine cyclic 3′: 5′-monophosphate were unsuccessful. Inhibition experiments indicate that probably one enzyme is involved in the hydrolysis of both of these substrates.